ANALISIS PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (Sekolah Tinggi Ilmu Ekonomi Atma Bhakti, 2013)
The purpose of this study was to analyze the effect of financial performance on stock returns on companies listed in Indonesia Stock Exchange. Financial performance was measured with the five financial ratios Return on Investment (ROI), Earning per Share (EPS), Debt Equity Ratio (DER), Price Earning Ratio (PER) and Price to Book Value (PBV). This study uses secondary data in the form of financial ratios, stock prices and manufacturing companies go public and actively traded on the Stock Exchange in 2007, 2008, 2009 and 2010. Sampling was based on purposive sampling technique and obtained a sample of 34 companies that match specified criteria. T-test hypothesis test results show that the partial debt equity rqtio(DER) negatively affect stock returns, price book value (PBV) positive effect on stock returns. Being variable return on investmen (ROI), earning per share (EPS) and price earning ratio (PER) has no effect on stock returns. F test results indicate that the financial performance of the ROI, EPS, DER, PER and PBV positive effect on stock returns. Results of testing the coefficient of determination (R2) indicates that only 17 % return variable is explained by the variable ROI, EPS, DER, PER and PBV. A percentage of 83 % in explained by other variables that are not addressed in this study.